INCREASING THE SECRECY OF TRANSMISSION INFORMATION BASED ON COMBINED RANDOM CODING - Korchynskyi, V. V.; Kildishev, V. I.; Holev, D. V.; Berdnikov, O. M. (Radio Electronics, Computer Science, Control, 2019)
Context. The task of increasing the secrecy of information transmission based on combined random coding is considered. The object of research is the integration processes of stochastic, block and timer coding. Objective. The aim of the article is to develop a method of increasing the secrecy transmission based on combined random coding. Method. The method of increasing the secrecy of information transmission based on combined random coding with three steps of code converters: internal, intermediate and external is proposed. The internal converter is implemented based on stochastic coding with various numbers of random code combinations. The number of random combinations depends on the probability of the character of the symbol in the message text. The information secrecy of the transmission is ensured by equalizing the probabilities of the occurrence of code combinations from the output of the statistical coder. Intermediate coding is implemented using a noise immunity block code. Information secrecy and noise immunity leads to the increasing the length of the code block at each stage of coding, which reduces the code rate. To solve this problem, an external converter based on timer coding is used. At this stage, binary combinations are converted into timer signal structures, which allows for the implementation of a structural transmission secrecy, increase the code rate and improve noise immunity. When the stochastic encoding and a timer used codebooks. Results. The developed method of combined random coding allows to increase the main indicators of noise immunity: interference protection, information and structural secrecy. Conclusions. The proposed method of combined random coding allows to eliminate the main disadvantages of stochastic coding, in which the choice of the number of random code combinations does not take into account the entropy of the discrete source of information. For solving this problem, it was proposed to use different number of random combinations, in view of the probability of an alphabet symbol appearing in the text. From the theoretical point of view, this will allow the output of the statistical coder to form a stream of combinations with equal probabilities of occurrence. Due to the usage of timer signal constructions, the problem of redundancy compensation is solved, which appears during stochastic and noise-immune coding.